PENERAPAN METODE CERTAINTY FACTOR UNTUK MENDETEKSI PENYAKIT HYDROCHEPALUS BERBASIS WEB - Badaruddin, Muliati (Teknosains: Media Informasi Sains dan Teknologi, 2016)
Hydrocephalus is disease that occurs resulting from disruption the flow of a liquid in the brain (a liquid serebro spinal) or accumulated cerebrospinal fluid in the ventricles of cerebral , the subarachnoid space , or space subdural. The disruption is causes the liquid the increase in many which then pressing brain tissue around it, especially nerve centers was vital . This research aims to devise an expert system that implements the method of Certainty Factor ( CF ) is the value of certainty factors as the value of clinical parameters given MYCIN to indicate the level of confidence is based on the hypothesis that are affected by symptoms (evidence ) of a disease. Expert systems are designed based on the knowledge of specialists and associated research on diseases Hydrocephalus is further applied on the expert system by applying the method certainty factor whose output can be seen through the medium of a computer connected to the Internet network , it is intended to be known by the public to anticipate and know the early symptoms of the disease Hydrocephalus and the prevention and early treatment of the disease before it 's too late to be addressed.